Disadvantaged Schools from the Perspective of Administrator: Solutions for Social Justice - Ali Tosun; Mustafa Hami Ay (Anı Publishing, 2020)
Economic, political and social developments worldwide created unfair situations in the distribution of interpersonal services and goods. This situation reflected in the education field which is one of the most important human rights and revived the concept of social justice in education. The aim of this study was to determine disadvantageous situations at school level which make it difficult to provide social justice in education, limitations and suggestions for the elimination of these situations. The data of the study was conducted with 23 participants who were working as school administrators and administrative assistants in public schools in Uşak. Semi-structured interview form was used as data collection tool. The data were analyzed by descriptive analysis technique. The views of the administrators have indicated that the factors, such as the human and physical resources of the school, students, parents and the environment of the school cause schools to be disadventageous. At the same time, although the school administrators have offered various suggestions for disadvantageous schools, they have emphasized that there are some limitations such as parents' attitudes, current legal regulations and time.